CPEB4-Promoted Paclitaxel Resistance in Ovarian Cancer In Vitro Relies on Translational Regulation of CSAG2 - Zhang, Yaqing; Gan, Hongyun; Zhao, Fei; Ma, Xiaomei; Xie, Xiaofeng; Huang, Rui; Zhao, Jin (Frontiers in Pharmacology, 2021)
Background: Drug resistance is a major obstacle in chemotherapy for ovarian cancer, wherein the upregulation of drug-resistant genes plays an important role. The cytoplasmic polyadenylation element binding protein 4 (CPEB4) is an RNA binding protein that controls mRNA cytoplasmic polyadenylation and translation. Methods: The expression of CPEB4 in paclitaxel-resistant ovarian cancer cell lines and recurrent ovarian tumors relative to counterparts was determined by qRT-PCR, Western blotting and immunohistochemistry. The response to paclitaxel treatment was evaluated by cellular viability test and colony formation assay. RNA immunoprecipitation and poly(A) tail test were applied to examine the levels of RNA binding and cytoplasmic polyadenylation. Results: CPEB4 is elevated in paclitaxel-resistant ovarian cancer cells and recurrent ovarian tumors treated with paclitaxel-based chemotherapy. In addition, CPEB4 overexpression promotes paclitaxel resistance in ovarian cancer cells in vitro, and vice versa, CPEB4 knockdown restores paclitaxel sensitivity, indicating that CPEB4 confers paclitaxel resistance in ovarian cancer cells. Mechanistically, CPEB4 binds with the taxol (paclitaxel)-resistance-associated gene-3 (TRAG-3/CSAG2) mRNAs and induces its expression at a translational level. Moreover, CSAG2 expression is upregulated in paclitaxel-resistant ovarian carcinoma and cancer cell lines, and more importantly, siRNA-mediated CSAG2 knockdown overtly attenuates CPEB4-mediated paclitaxel resistance. Conclusions: This study suggests that the drug-resistant protein CSAG2 is translationally induced by CPEB4, which underlies CPEB4-promoted paclitaxel resistance in ovarian cancer in vitro. Thus, interfering CPEB4/CSAG2 axis might be of benefit to overcome paclitaxel-resistant ovarian cancer.